Iron bromide vapor laser; Technical Physics Letters; Vol. 42, № 3 - Sukhanov V. B. Viktor Borisovich; Shiyanov D. V. Dmitry Valeryevich; Trigub M. V. Maksim Viktorovich; Dimaki V. A. Viktor Anatoljevich; Evtushenko G. S. Gennady Sergeevich (2016, 2016)
Title screen